WHO report on the global tobacco epidemic, 2008 : the MPOWER package (World Health Organization, 2008)
This landmark new report presents the first comprehensive worldwide analysis of tobacco use and control efforts. It provides countries with a roadmap to reverse the devastating global tobacco epidemic that could kill up to one billion people by the end of this century. The report outlines the MPOWER package, a set of six key tobacco control measures that reflect and build on the WHO Framework Convention on Tobacco Control.